Principles of Economic Ibn Taymiyyah (Moral Analysis) - Duriana Duriana (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2015)
This paper discusses the economic principles of Ibn Taymiyyah with moral analysis. The purpose of this paper is to reveal the position of morality in economic principles of Ibn Taymiyyah. There are two issues to be answered in this paper are: how is the economic principles of Ibn Taymiyyah, and how is the moral position in the economic principles of Ibn Taymiyyah. This research was found: principles of Ibn Taymiyyah's economy include: the principle of balance, fairness, sharia, cooperation, consultation and the prohibition of usury. Moral position in the economic principles of Ibn Taymiyyah is the basis and foundation of the economy which is essentially based on justice as a moral parent intended to protect the public from a variety of exploitative actions.